Depressive symptoms and professional satisfaction in Greek nursing personnel in the realm of European financial crisis - Karanikola, Maria; Zartaloudi, Afroditi (My University, 2021)
Background: The ongoing economic crisis in Europe, including Greece, has been linked with increased psychiatric morbidity and financial rewards reduction, both related to job dissatisfaction. Aim: We explored among Greek nursing personnel the degree of satisfaction from wages, and associations with depressive symptoms and total professional satisfaction. Also, associations with socio-demographic, educational and employment variables were explored. Methods: A cross-sectional study was applied (July to August 2015). A census sample of 66 members of nursing personnel employed in a randomly selected Greek public hospital completed the Index of Work Satisfaction and the Center for Epidemiological Studies-Depression scale. Descriptive and inferential statistics were applied. Results: The response rate was 73.4%. The degree of satisfaction from wages was low [mean (SD) = 2.1(0.13)-scale range/item 1–7], and strongly positively associated with total professional satisfaction (r = 0.419, P = 0.005). Also, those working in morning shift reported higher degree of work satisfaction from wages (P = 0.05) compared to those working in rotation shifts. Total professional satisfaction was moderate [mean (SD)/item = 3.93(0.05)-scale range/item: 1–7]. Higher depressive symptom values were observed in deputy head nurses compared to nursing assistants (P = 0.011) and staff nurses (P = 0.02), as well as in employees working in morning shifts compared to those working in rotation shifts (P = 0.013). Conclusions: An association between satisfaction from wages and total professional satisfaction was noted; yet, there was no link of depressive symptoms with satisfaction from wages, or total professional satisfaction. Instead, satisfaction from wages and intensity of depressive symptoms were associated with organizational/administrative polices and employment variables.
Keywords: Depression; Nursing; Job satisfaction; Financial; Greece